(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The advancement of technology has had a significant impact across various sectors, including the accounting field. Gradually yet inevitably, technological developments are transforming accounting practices, which in turn are reshaping the role of accountants. This phenomenon raises an important question: does technology pose a threat to the accounting profession, or does it instead offer broader opportunities? This study examines whether technological advancement in accounting represents a threat or an opportunity through a service-learning intervention. The program involved 40 vocational accounting students and employed a pre-test and post-test design analyzed using a paired sample t-test. The results showed a significant improvement in students’ understanding (p < 0.05), including a 57% increase in awareness of the relationship between technology and accounting and a 46% increase in interest in pursuing accounting careers. The findings indicate that technology should be viewed as a strategic tool rather than a replacement for accountants. This study highlights the effectiveness of service-learning in improving students’ professional literacy and readiness for the digital era.